2020
DOI: 10.1002/smll.202002885
|View full text |Cite
|
Sign up to set email alerts
|

Exploration and Investigation of Periodic Elements for Electrocatalytic Nitrogen Reduction

Abstract: electron affinity (−1.9 eV) make direct hydrogenation of N 2 a thermodynamically forbidden process. [14,15]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 329 publications
0
56
0
Order By: Relevance
“…Electrocatalytic nitrogen reduction reaction (NRR) under mild condition is a new and alternative artificial nitrogen fixation technology with environmentally friendly feature using water as the hydrogen source, showing great potential to solve the above problems. [146,147] However, N 2 fixation is a very difficult reaction because of its inherent properties, such as extremely high bond energy (940.95 kJ • mol À 1 ) and no permanent dipole in the N�N triple bond. From the perspective of kinetic barrier, there is a large energy gap between the highest occupied and the lowest unoccupied orbitals, which is not conducive to the electron transfer reaction.…”
Section: Application Of Ceo -Based Electrocatalysts In Nrrmentioning
confidence: 99%
“…Electrocatalytic nitrogen reduction reaction (NRR) under mild condition is a new and alternative artificial nitrogen fixation technology with environmentally friendly feature using water as the hydrogen source, showing great potential to solve the above problems. [146,147] However, N 2 fixation is a very difficult reaction because of its inherent properties, such as extremely high bond energy (940.95 kJ • mol À 1 ) and no permanent dipole in the N�N triple bond. From the perspective of kinetic barrier, there is a large energy gap between the highest occupied and the lowest unoccupied orbitals, which is not conducive to the electron transfer reaction.…”
Section: Application Of Ceo -Based Electrocatalysts In Nrrmentioning
confidence: 99%
“…However, as the potential increases [exceed −0.5 V (vs RHE)], the production of NH 3 and FEs is rapidly decreasing, which may be caused by the competitive adsorption of nitrogen and H + /H 2 on FeS 2 −MoS 2 @IF x . 56 For comparison, the NRR activities of FeS 2 −MoS 2 @IF 100 , FeS 2 −MoS 2 @IF 300 , FeS 2 − MoS 2 @IF 400 , FeS 2 @IF, and MoS 2 were examined under the identical conditions (Figure S14−S18). The NH 3 yield of FeS 2 −MoS 2 @IF x (x = 100, 300, and 400), MoS 2 , and FeS 2 @IF is approximatively 2.9, 4.2, 2.5, 1.4, and 3.4 × 10 −10 mol s −1 cm −2 , which is suggesting that FeS 2 −MoS 2 @IF 200 (7.1×10 −10 mol s −1 cm −2 ) is highly active for the NRR, further highlighting the important role of the two-phase rational interface engineering and relatively large SSA for NRR activity (Figure 6f).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The NRR is a reaction of recent large interest, with over 50 reviews on this topic published in the last few years, mainly focused on the electrocatalytic synthesis and related materials, a selection of which is given in ref. [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] More limited studies deal with the photochemical NRR, while essentially no studies on PEC-type devices for NRR have been reported. The interest on this reaction derives from the possibility to reduce up to 90% the carbon footprint with respect to the current method of synthesis (Haber-Bosch process), which meets the current need for large quantities of ammonia, a key component towards fertilizers and as hydrogen or energy vector.…”
Section: Energy and Environmental Science Perspectivementioning
confidence: 99%